Dynamics of Predator-prey Interactions in Sharp Tooth Catfish (Clarias gariepinus; Burchell, 1822) and Carp Fingerlings (Labeo bata; Hamilton, 1822) with Special Reference to the Development of Anti-Predatory Strategies - Chakraborty, Deep Chandan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This study explores the dynamics of predator-prey interactions and functional response of Clarias gariepinus (African Magur/Sharptooth Catfish - predator) and of Labeo bata (Carp fingerlings - prey). Author investigated the behavioral patterns of both species in isolation and during encounters, exploring the impacts of predator size, prey-predator ratio, encounter duration and placement of separators on anti-predatory strategies. Results indicated that prey behavior is influenced by predator presence, with crowding, hiding, and inspection emerging as key anti-predatory strategies. The development and intensity of these strategies are intricately linked to prey-predator ratio, size difference, and encounter duration. Notably, larger predators trigger more pronounced anti-predatory responses in preys, while high prey composition motivates individuals to inspect predators, conveying fearlessness and fitness. Findings provide valuable insights into the evolution of predator-avoidance behaviors in prey species, sheds light on the complex dynamics governing predator-prey interactions in aquatic ecosystems.